Quantification of the safety against groundwater ingress through longitudinal joints of segmental tunnel linings by means of convergences. (June 2023) - Zhang, Jiao-Long; Yuan, Yong; Liu, Xian; Mang, Herbert A.; Pichler, Bernhard L.A.
Abstract: Conventional inspection of groundwater leakage of segmental tunnel linings is a time-consuming task, while vertical and horizontal convergences are routinely measured in many tunnels. This provides the motivation to use convergences as input for the quantification of the safety against groundwater ingress through longitudinal joints of segmental tunnel linings. Measured convergences are translated into relative rotations at the joints. These rotations are then converted to changes of the compression of the gaskets. Combining these changes with results from testing of the gaskets allows for quantification of the remaining sealing pressure. The safety against groundwater ingress is quantified by means of the ratio between the remaining sealing pressure and the groundwater pressure. To ensure efficient application in tunnel engineering, closed-form equations are provided in the analysis whenever possible. The method is validated by comparing model predictions with inspection data of the segmental lining of Metro Line 7, in Shanghai. Finally, the effectiveness of two sets of gaskets per longitudinal joint is assessed. It is concluded that a symmetric arrangement of two pairs of gaskets, one close to the outer edge and the other close to the inner edge of the joint, significantly increases the water tightness as long as the sealing of the bolt channels can be guaranteed. Otherwise, an eccentric arrangement of two pairs of gaskets, both close to the outer edge, is a good option. Highlights: The safety against water ingress is quantified by means of convergences. Known convergences are converted into relative rotations at the joints. They are converted into the deformation of the gaskets. The related gasket sealing pressure is compared with groundwater pressure. Successful validation motivates the analysis of systems with two sets of gaskets.